2019
DOI: 10.1002/ldr.3282
|View full text |Cite
|
Sign up to set email alerts
|

Mapping European ecosystem change types in response to land‐use change, extreme climate events, and land degradation

Abstract: Extreme climate events and nonsustainable land use are important drivers altering the functioning of European ecosystems, resulting in loss of the services provided. Yet a consensus method for regular continental scale assessment of ecosystem condition in relation to land degradation (LD) is still lacking. Here, we propose a new remote sensing‐based approach allowing for improved, repeated assessment of changing pressure on terrestrial ecosystems. On the basis of segmented trend analysis of water‐use efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 54 publications
(100 reference statements)
1
28
0
Order By: Relevance
“…Such improvements represent important steps towards the comprehensive analysis of pathways of change in ecosystem functioning. For example, it was recently shown that local degradation processes (e.g., decreased vegetation productivity owing to soil erosion) would be signalled by a change in the magnitude of the slope, suggesting a slowing down in ecosystem functioning (Horion et al, 2019). Thanks to our new typology, acceleration and slowing down of ecological processes can now be captured and labelled in a systematic way.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such improvements represent important steps towards the comprehensive analysis of pathways of change in ecosystem functioning. For example, it was recently shown that local degradation processes (e.g., decreased vegetation productivity owing to soil erosion) would be signalled by a change in the magnitude of the slope, suggesting a slowing down in ecosystem functioning (Horion et al, 2019). Thanks to our new typology, acceleration and slowing down of ecological processes can now be captured and labelled in a systematic way.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of ecological inference for the types of ecosystem changes are given in Table 1. However, it is important to note that different drivers or combinations of drivers may result in the same type of ecosystem change (Horion et al, 2019). Further research is needed to deepen our knowledge on the variability of ecosystem pathways resulting from single or combined driving forces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations